The Influence of Organizational Resilience on SME Firm Performance: A Conceptual Model - Hu, Yuefen; Choi, Sang Long; Tan, Shen Kian (Business Management and Strategy, 2024)
SMEs’ performance has been affected due to the pandemic situation, and managers should pay attention to the changing external environment and adjust their business strategies. For long-term business sustainability, organizational resilience is nevertheless an important factor that enables SME businesses to mitigate the disruption caused by the innate uncertainty presented in the environment. This paper extends the research on the development of organizational resilience in the field of business management by doing a complete literature review and proposing a link between organizational resilience and firm performance. The findings of this study indicate that there is a considerable association between organizational resilience and firm performance. The proposed conceptual framework will make significant contributions to future studies.